Analysis and Evaluation of International Natural Honey Markets - Castro Fajardo, Hermes; Otálora Gómez, Lina María; Chavarro Miranda, Fernando (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The research aims to classify the countries to guide the internationalization of natural honey producers in Colombia by applying the matrix of attractiveness and competitiveness, since the current market demands from companies actions that generate competitive advantages to face the growing international competition and seize its opportunities. The matrix of attractiveness and competitiveness, explained here, guides the decision about where and how to enter international markets, for this, the Boston Consulting Group (BCG) matrix was adapted in its original axes by per capita consumption and market growth to locate the target countries in quadrants according to the life cycle of the product (introduction, growth, maturity and obsolescence) or with axes of per capita consumption and apparent price to locate competitive strategies (leadership in costs, differentiation and focus), facilitating the design of international marketing plans. The research shows that France is positioned as the market with the greatest potential to be approached with the possibility of national producers to offer value propositions based on differentiation and focus.